2015
DOI: 10.1037/a0038951
|View full text |Cite
|
Sign up to set email alerts
|

Time spent in child care: How and why does it affect social development?

Abstract: Children who experience early and extensive child care, especially center-based care, are rated by teachers as having more externalizing behavior problems than are other children. This association is reduced, but not eliminated, when care is of high quality, and it varies by socioeconomic disadvantage and the type of behavior assessed. We examine the processes that may account for the quantity effect, concluding that it occurs primarily among relatively advantaged White non-Hispanic families. It appears primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
67
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 102 publications
9
67
2
1
Order By: Relevance
“…Positive associations between more time on Head Start and socioemotional outcomes are consistent with prior evidence that has indicated that negative associations between amount of ECE and socioemotional outcomes are non-significant for lowincome students, and have stronger negative associations for white non-Hispanic children (Huston et al, 2015). However, it is still unclear why there are some negative associations between amount of ECE and socioemotional outcomes, and the associations between dosage and self-regulation more specifically using direct measures.…”
Section: C Two Versus One Year Of Head Start and Child Outcomessupporting
confidence: 76%
See 4 more Smart Citations
“…Positive associations between more time on Head Start and socioemotional outcomes are consistent with prior evidence that has indicated that negative associations between amount of ECE and socioemotional outcomes are non-significant for lowincome students, and have stronger negative associations for white non-Hispanic children (Huston et al, 2015). However, it is still unclear why there are some negative associations between amount of ECE and socioemotional outcomes, and the associations between dosage and self-regulation more specifically using direct measures.…”
Section: C Two Versus One Year Of Head Start and Child Outcomessupporting
confidence: 76%
“…There is evidence supporting the notions that, less absence and a greater number of years (two versus one) in ECE are related to better academic and behavioral outcomes (Arbour et al, 2016;, while the number of hours a week is mostly related to externalizing behavior (Huston et al, 2015).…”
Section: Dosage: Amount Of Early Childhood Education Experiencesmentioning
confidence: 83%
See 3 more Smart Citations